Solid/liquid separation : equipment selection and process design - Tarleton, E. Steve; Wakeman, Richard J. (Elsevier/Butterworth-Heinemann, 2007)
In this volume, the third in a set specifically written for the industrial process and chemical engineer, the authors provide the detailed information on filtration equipment and media which allows the reader to then consider the pre-treatment of suspensions, selection of the most appropriate equipment for the task, data analysis and the subsequent design of the processes involved for particular separations. The result is a comprehensive book which is designed to be used frequently and referred to regularly in order to achieve better industrial separations. Successful industrial-scale separation of solids from liquids requires not only a thorough understanding of the principles involved, but also an appreciation of which equipment to use for best effect, and a start-to-finish plan for the various processes involved in the operation. If these factors are all correct, then successful separations should result. *Part of 3-volume set *Unique approach to industrial separations *Internationally-known authors
"IChemE
Includes bibliographical references (p. [391]-409) and index
Keywords: Separation (Technology); Separators (Machines); elektronické knihy; electronic books